Synergistic interaction of eugenol and antimicrobial drugs in eradication of single and mixed biofilms of Candida albicans and Streptococcus mutans - Jafri, Huma (AMB Express, 2020)
In vitro eradication of the C. albicans and S. mutans mixed biofilms by eugenol alone and in combination with the antimicrobial drugs. Previously characterized strains of C. albicans (CAJ-01 and CAJ-12) and S. mutans MTCC497 were used to evaluate the eradication of biofilms using XTT reduction assay, viability assay, time dependent killing assay and scanning electron microscopy (SEM). Synergistic interaction was assessed by checkerboard method. Sessile MIC (SMIC) of eugenol was equivalent to the planktonic MIC (PMIC) against C. albicans and S. mutans mixed biofilms. SMIC of fluconazole and azithromycin was increased upto 1000-folds over PMIC. Eradication of single or mixed biofilms was evident from the viability assay and SEM. At 1 × MIC of eugenol, log(10)CFU count of C. albicans cells were decreased from 6.3 to 4.2 and 3.8 (p < 0.05) in single and mixed biofilms, respectively. SEM studies revealed the eradication of C. albicans and S. mutans cells from glass surface at 800 µg/mL concentration of eugenol. Time dependent killing assay showed dose dependent effect of eugenol on pre-formed CAJ-01, CAJ-12 and S. mutans biofilm cells. Eugenol was highly synergistic with fluconazole (FICI = 0.156) against CAJ-12 single biofilms. However, the combination of eugenol and azithromycin showed maximum synergy (FICI = 0.140) against pre-formed C. albicans and S. mutans mixed biofilms. These findings highlighted the promising efficacy of eugenol in the eradication of biofilms of two oral pathogens (C. albicans and S. mutans) in vitro and could also be exploited in synergy with fluconazole and azithromycin in controlling oral infections.